2019
DOI: 10.21307/jofnem-2019-067
|View full text |Cite
|
Sign up to set email alerts
|

Touch-stimulation increases host-seeking behavior in Steinernema Carpocapsae

Abstract: Previous research demonstrated that Steinernema carpocapsae infective juveniles (IJs) exposed to a host cuticle were more attracted toward certain host-associated volatile odors. We wanted to test the specificity of attraction that results from exposure to host cuticle. Host recognition behavior was analyzed after stimulating IJs by allowing them to physically interact with Galleria mellonella cuticles. The subsequent behavioral response and the proportion of the population participating in chemotaxis to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…There are some particular parallels that can be drawn between the responses seen in the PF127 assays utilized in this study and those seen in the studies using agar-based media. The first is that the CI values in response to prenol are similar to those shown in previous studies, which have revealed that prenol is a repulsive chemotactic cue for several EPN species [5,17,18]. However, it is worth noting that in previous studies, which used agar-based assays, EPN IJs responded more strongly to prenol, yielding lower CI values (more negative) than we observed using PF127 media.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There are some particular parallels that can be drawn between the responses seen in the PF127 assays utilized in this study and those seen in the studies using agar-based media. The first is that the CI values in response to prenol are similar to those shown in previous studies, which have revealed that prenol is a repulsive chemotactic cue for several EPN species [5,17,18]. However, it is worth noting that in previous studies, which used agar-based assays, EPN IJs responded more strongly to prenol, yielding lower CI values (more negative) than we observed using PF127 media.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to finding that the general response to prenol was congruent with the data from agar-based assays, the corresponding participation data reflect the findings by the CI values; similar to previous EPN behavioral work that has measured participation (i.e., participation reflects movement towards the control region of the plate) [5,17,18]. Unexpectedly, our use of the participation measurements revealed that the proportion of IJs not participating (i.e., remaining in the center) across most species was lower and did not vary as much as has been reported in previous studies [5,18].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Steinernema glaseri responds to exposure to host cuticle by switching its searching behavior from ranging (which is typically occurs when no host cues are present) to area-concentrated (which signifies the recognition of host cues nearby) (Lewis et al, 1992). Steinernema carpocapsae IJs are significantly more attracted to volatile cues produced by hosts after exposure to G. mellonella cuticle (Lewis et al, 1995b;Baiocchi et al, 2019) and indeed respond most strongly to exposure to the cuticle of potential hosts that support high levels of reproduction (Lewis et al, 1996). Thus, we are confident that changes in the lead IJ as a result of exposure to host cuticle account for following of subsequent conspecific IJs.…”
Section: Discussionmentioning
confidence: 99%
“…Putative attractants and repellents were chosen based on the literature: methyl salicylate (Chaisson and Hallem, 2012), acetone (O'Halloran and Burnell, 2003), prenol (Baiocchi et al, 2017(Baiocchi et al, , 2019Kin et al, 2019) and hexanol (O'Halloran and Burnell, 2003;Chaisson and Hallem, 2012). Prenol (3-methyl-2-buten-1-ol) was diluted to 2 M, by mixing 203 μL of 99.9% prenol (Sigma-Aldrich, UK) with 797 μL of ethanol as per Baiocchi et al (2017).…”
Section: Chemotaxis Assaysmentioning
confidence: 99%